The conceptual vision of the uniqueness judgement in contemporary interior design techniques (Journal of Architectural Design, 2022)
In the past 20 years, modern societies have witnessed the milestones of a new civilizational renaissance. This has resulted from a tremendous growth in the development and use of design techniques, which has changed many concepts in technical and engineering sciences. This in turn has required the interior designer to study his/her conceptual scientific and practical vision to judge the uniqueness in the production of contemporary design techniques that ensure the ability to distinguish, attract and understand and suit human activity in presenting distinctive designs for the interior space. The problem and importance of research can be summed up by the following question: what is the designer’s conceptual vision of judging uniqueness in contemporary interior design techniques? The second section of this study included the theoretical framework and its emerging subsections that took into account the subject of the conceptual vision and its relationship by virtue of the uniqueness of the interior designs. The research procedures were given within the third section where two models of interior designs of restaurants were analysed in China. The most important results were that the role of design production was reflected through experience and knowledge in contemporary techniques achieved in the design of interior determinants in both models, with its relative materialisation in the ceiling of the second model. The achievement of dominance in the design of the ceiling and the floor and its relative materialisation in the walls of the first model emerged while dominance was achieved within the walls of the second model and did not materialize in the ceiling and floor. As for the element of attraction that distinguishes the design and reflects its uniqueness, it was achieved through the design of the interior determinants in the first model, as well as in the walls with its relative materialisation in the floor of the second model.